2014
DOI: 10.1038/srep05837
|View full text |Cite
|
Sign up to set email alerts
|

Hf-Nd isotopic variability in mineral dust from Chinese and Mongolian deserts: implications for sources and dispersal

Abstract: Mineral dust provenances are closely related to the orogenic processes which may have distinct Hf-Nd isotopic signatures. Here we report the clay-sized (<2 μm) Hf-Nd isotope data from Asian dust sources to better constrain the source and transport dynamics of dust deposition in the North Pacific. Our results show that there is a more positive radiogenic Hf isotopic composition with clay-sized fractions than the corresponding bulk sample and a decoupling of the Hf-Nd couplets in the clay formation during the we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
81
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 59 publications
(90 citation statements)
references
References 59 publications
9
81
0
Order By: Relevance
“…Sun et al, 2000;Ding et al, 2002;Gallet et al, 1996). While these methods can still provide valuable insights into source via analysis of potential mixing lines in data (Zhao et al, 2014), they have the disadvantage of averaging out multiple distinct sediment source signatures. As such, more recent studies have used single-grain approaches such as detrital zircon U-Pb geochronology on Chinese Plateau Loess (Stevens et al, 2010(Stevens et al, , 2013bPullen et al, 2011;Che & Li 2013;Xiao et al, 2012;Nie et al, 2014) and loess deposits elsewhere (e.g.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Sun et al, 2000;Ding et al, 2002;Gallet et al, 1996). While these methods can still provide valuable insights into source via analysis of potential mixing lines in data (Zhao et al, 2014), they have the disadvantage of averaging out multiple distinct sediment source signatures. As such, more recent studies have used single-grain approaches such as detrital zircon U-Pb geochronology on Chinese Plateau Loess (Stevens et al, 2010(Stevens et al, , 2013bPullen et al, 2011;Che & Li 2013;Xiao et al, 2012;Nie et al, 2014) and loess deposits elsewhere (e.g.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Provenance studies using both using Nd-Sr isotopic composition (Chen and Li, 2011;Zhao et al, 2014) and detrital zircon U-Pb age analyses (Xie et al, 2012) have demonstrated that the major source areas of the loess deposits in NE China are likely to be the upwind Horqin and Otindag sandy deserts. Therefore, the loess and adjacent sandy deserts Catena 154 (2017) [21][22][23][24][25][26][27][28][29][30][31][32] in NE China can be regarded as a coupled system, with dust source and sink formed under a semi-arid climate, which is quite distinct from the loess deposits of the CLP and their corresponding sources areas in northwestern and central China.…”
Section: Introductionmentioning
confidence: 99%
“…The Hf isotopic tracer has recently been used in dust source fingerprinting for marine sediments (e.g., Pettke et al, ), modern aerosols/soils (Aarons et al, ; Pourmand et al, ; Zhao et al, ) and dust in ice cores (Blakowski et al, ; Lupker et al, ; Újvári et al, ). Hafnium isotopic ratios do not seem to be affected by weak acetic acid applied in this study (Újvári et al, ), which is similar to Nd isotopes.…”
Section: Discussionmentioning
confidence: 99%
“…Hafnium isotopic ratios do not seem to be affected by weak acetic acid applied in this study (Újvári et al, ), which is similar to Nd isotopes. The 176 Hf/ 177 Hf isotopic compositions have an apparent grain size dependence: these are always more radiogenic in the fine fractions of dust/loess than in the bulk samples (Újvári et al, ; Zhao et al, ). Aerosol samples in dust plumes proved also to be more radiogenic in Hf with increasing distance from the source region (Aarons et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation